Foreign Banking and Investment in the United States : Issues and Alternatives - Lees, Francis A. (New York : Wiley, 1976)
This volume focuses on the second aspect of the international banking role of the U.S., namely the growth of foreign bank representation and operations in America.
"A Halsted Press book."
Includes index.
Bibliography: p. [155]-158.
osc 15/08/17
Loans
Keywords: Banks and Banking, Foreign; Investments, Foreign